STUDI PENGELOLAAN ZAKAT DI MALAYSIA - AHMAD WIRA (Maqdis: Jurnal Kajian Ekonomi Islam, 2019)
The study of zakat in Malaysia is very interesting when it is associated with the way it is managed. Malaysia is one of the countries that regulates the issue of zakat, even though it is determined by the power of each country. In Malaysia there is no zakat law in the rank of nationality which can unite the zakat management system. In addition, the management of zakat is also still based on the policies of the territories of the fellowship and their respective countries. The management of zakat in Malaysia must determine the direction and have clear ownership in the management of zakat assets collected from muzakki. The objectives in the management of zakat are always directed to: First, increase zakat and payers levies. Secondly, it facilitates the rules of zakat payment. Third, educating Muslims about the obligation to pay alms. Fourth, introducing corporate management in zakat collection by using information and communication technology (ICT).